Digital Red Book: An Improvement of The Conventional Pregnancy Monitoring System Via Digitalization - Abdul Halim Bin Omar; Muhammad Naim Adha Bin Abdullah; Abdul Azim Bin Jamalulais; Syed Muhammad Afiq Bin Syed Masahor (Multidisciplinary Applied Research and Innovation, 2023)
Digital Red Book : An Improvement of the Conventional Pregnancy Monitoring System Via Digitalization is built to assits medical officers to monitor the baby’s development and the mother of the child until the child reaches the age of six years old and replace the conventional red book that have been used since the 1980s. This project aim to develop a system for medical officers to monitor the development of child and the mother. The development method that we use is the Software Development Life cycle was employed in this project to generate a complete overview of the ryhtms watch inventory system. Previously government medical officers use what is to be called the ‘Red book’ which contain information about child growth which was out of style compared to this era. This method is obsolete and could lead to misinformation and inefficient data storage. Our end result for this project is fully integrated personal pregnancy data storage which will display all information regarding the doctor’s visitation and pregnancy stage. Users can also review the data that are stored in the system which is confidential towards other users. The system will provide an efficient way of data storing and information transfer for medical purposes.